Социальный институт: функция, генезис, структура - Матусевич, В. (Социология: теория, методы, маркетинг, 2004)
The article deals with definition of “social institution” as a unity of its genetic, functional and structural characteristics. There are discussed pre -conditions and determinants of social regulation being an attributive feature of institutions, its normative and organizational elements, comparative analysis of legal and moral kinds of social institutions.